Arte e psicanálise: um estudo sobre o pathos em Édipo e Hamlet - Ferreira, Ezequiel Martins (2015)
The relationship between art and psychoanalysis is established since the emergence of the latter, throwing the concept of the unconscious world. On the way done in this dissertation is possible to question this relationship, following it from the following points: taking art as the biographical and autobiographical scheme, taking it as connected to sublimate and finally looking set it as the outline of the empty. In the latter sense has the art as a testimony of how the unconscious operates. To explain the unconscious manifestation in the art were used two tragedies that occupy a privileged place in very theoretical construction of psychoanalysis: Oedipus and Hamlet. For this, the authors were consulted from inside and outside the psychoanalytic field as Freud, Lacan, Rancière and Brecht. Note that the concept of pathos emerges as a nodal point, able to see through the plays, the unconscious operation. In addition to the parts, appear at the end of this dissertation, in order to continue the discussion of a "beyond the Oedipus complex," the four fundamental discourses as a third example of the unconscious functioning.